Seven new species of Licuala (Livistoninae, Arecaceae) from New Guinea - Barfod, Anders S.; Heatubun, Charlie D. (Phytotaxa, 2022)
Based on newly gained insights from intensified fieldwork, we describe seven new species of Licuala from New Guinea and adjacent islands. All species are illustrated and provided with information on their habitat, conservation status and morphological affinities.